Effect of Marble Particle on Physico-Mechanical behaviour of Glass Fiber Reinforced Epoxy Composites - Ray, Subhrajit (International Journal of Integrated Engineering, 2019)
Materials with superior properties have been used to meet the demand for better operational performance in the world of advanced science and technology. To fulfil such needs, the importance of industrial usage of polymer composite materials filled with industrial waste instead of high cost ceramic filler has tremendously increased. In this present work, new classes of glass fiber reinforced epoxy composites with different weight content of marble powder are prepared by simple hand layup technique. Different mechanical properties test were conducted. The experimental study reveals that new hybrid composites shows better impact and hardness resistance compared with unfilled composite, while tensile and flexural strength of the composite decreases. This may be due to the presence of marble particles and a void on the upper surface induces stress concentration zone resulting crack propagation on the matrix region which increases with the addition of filler material.